Euro Area Monetary Policy in Uncharted Waters - Stavrev, Emil.; Cihak, Martin; Harjes, Thomas (Washington, D.C. : International Monetary Fund, 2009)
We analyze the European Central Bank's (ECB's) response to the global financial crisis. Our results suggest that even during the crisis, the core part of ECB's monetary policy transmission-from policy rates to market rates-has continued to operate, but at a decreased efficiency. We also find some evidence that the ECB's non-standard measures, namely the lengthening of the maturity of monetary policy operations and the provision of funds at the fixed rate, reduced money market term spreads, facilitating the pass-through from policy to market rates. Furthermore, the results imply that the substantial increase in the ECB's balance sheet may have contributed to a reduction in government bond term spreads.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet